THE INFLUENCE OF STORE ATMOSPHERE ON PURCHASE DECISION AND IT’S IMPACT ON CUSTOMER’S SATISFACTION (Case study on Indomaret Customers JL. Raya Tlogomas No. 37, Malang) - Nizar Satya Diawan; Andriani Kusumawati; M. Kholid Mawardi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2016)
Penelitian ini bertujuan untuk: Pengaruh Store Atmosphere terhadap Purchase Decision, Pengaruh Store Atmosphere terhadap Customer Satisfaction, Pengaruh Purchase Decision terhadap Customer Satisfaction. Hasil penelitian menunjukkan bahwa: variabel Store Atmosphere memiliki pengaruh signifikan terhadap Purchase Decision. Variabel Store Atmosphere memiliki pengaruh signifikan terhadap Customer Satisfaction. Purchase Decision memiliki pengaruh signifikan terhadap Customer Satisfaction. Dengan demikian, manajemen Indomaret JL. Raya Tlogomas No. 37, Malang sebaiknya mempertahankan dan meningkatkan Store Atmosphere. Setelah diketahui bahwa Store Atmosphere memiliki pengaruh yang signifikan terhadap Purchase Decision, maka manajemen Indomaret dapat meningkatkan Store Atmosphere melalui fasilitas, layanan tambahan, tempat parkir dan semua aspek yang mempengaruhi keputusan pembelian konsumen. Kata Kunci: Store Atmosphere, Purchase Decision, Customer Satisfaction. ABSTRACT This research objectives are to: examine the influence of Store Atmosphere on Purchase Decision, examine the influence of Store Atmosphere on Customer Satisfaction, examine the influence of Purchase Decision on Customer Satisfaction. The result of path analysis showed that: Store Atmosphere has significant influence on Purchase Decision; Store Atmosphere has significant influence on Customer Satisfaction; Purchase Decision has significant influence on Customer Satisfaction. Therefore, the Management Indomaret JL. Raya Tlogomas No. 37, Malang should maintain and improve the store atmosphere. Since store atmosphere variable have a significant influence in affecting purchase decision, management of Indomaret could improve the store atmosphere through the facilities, additional service, parking space and all aspect that influence customer purchase decision. Key words: Store Atmosphere, Purchase Decision, Customer Satisfaction.